Genetic diversity based on RAPD markers of third-generation (M3) soybean mutant at saline soil. Issue 1 (July 2021) - Anwar, Syaiful; Lukiwati, Dwi Retno; Kusmiyati, Florentina
Abstract: Genetic diversity is very important in plant breeding. One way to create genetic diversity is through induced mutation. The purpose of this study was to evaluate genetic diversity based on RAPD markers of third-generation (M3 ) soybean mutant at saline soil. Seed of soybean cv. Detam was induced mutation by gamma rays at 0 (control), 160, 208, 256, 304, 352, 448, 496, 544 and 592 gy in Centre for Application of Isotope and Radiation – National Nuclear Energy Agency of Indonesia. First generation (M1 ) of those seed was planted at saline soil and selected based on plant production at saline soil. Those selected plants from M1 generation were planted at non saline soil as M2 generation. Selection on M2 was also done based on plant production. There were 13 genotypes selected from M2 as plant material for third-generation (M3 ) that were grown at saline soil. Genetic diversity based on RAPD markers using 6 primers namely G1, G2, OPAA-01, OPAA-02, OPAA-09, and OPAA-14. These markers were specific markers for soybean tolerance in salinity stress. The results showed that six markers generated 389 bands, ranging in size from 304 to 1710 bp. Cluster analysis using UPGMA procedure in the NTSYS PC Software program showed dendogram with two clusters. Genotypes of BSMG 02-256-7 and BSMG 02-592-9 had genetic distance of 15 % with the other eleven genotypes and control variety. It can be concluded that there was genetic diversity based on RAPD markers of third generation (M3 ) soybean mutant genotypes at saline soil.